Photo-electro-mechanical micro-cavity accelerometer based on quantum limited stark effect and preparation method thereof
By adopting the indium gallium nitrogen quantum well optoelectromechanical microcavity structure based on the quantum restricted Stark effect in the optical accelerometer, the complex design and processing problems in the prior art are solved, and a high sensitivity and anti-interference accelerometer is realized, with the advantages of miniaturization and low cost.
Patent Information
- Application Number
- CN202411938716.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
There are problems with beam length and mass influence in the design of existing optical accelerometers, which is difficult to take into account the possibility of realizing the quantum restricted Stark effect and actual processing, and the device wiring position affects normal operation.
An indium gallium nitride quantum well photomechanical microcavity accelerometer based on the quantum restricted Stark effect is used, and a silicon-based nitride epitaxial sheet is used as a carrier. Through reasonable process steps such as optical lithography and ICP etching processes, a beam accelerometer is prepared, and a reasonable electrode structure and SiO2 layer distribution is designed to achieve laser frequency wavelength changes to perceive acceleration.
It realizes the advantages of miniaturization, low cost, high sensitivity, resistance to electromagnetic interference and impact of the accelerometer, while simplifying the structural design and improving the integration convenience.
Smart Images

Figure CN119780471A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of quantum electronics and optomechanical technology, and in particular relates to an optomechanical microcavity accelerometer based on quantum confined Stark effect and a preparation method thereof. Background Art
[0002] The accelerometer is an important component of the inertial navigation system. The optical accelerometer is a new type of accelerometer with the advantages of miniaturization, low cost, high sensitivity, anti-electromagnetic interference and anti-shock. However, the current optical accelerometers all use passive materials such as SI and SIN. The sensing components themselves do not emit light and need to integrate external light sources, which limits high-density optoelectronic integration. The following technical problems currently exist: The design of a beam plus a mass block for the overall accelerometer must take into account the influence of the beam length on the luminescence, the influence of the mass block, the realization of the quantum confined Stark effect, and the feasibility of realization in the actual processing process.
[0003] When wiring the device, consider that the wiring position should not affect the normal operation of the device. Summary of the invention
[0004] To solve the above problems, the present invention discloses an optomechanical microcavity accelerometer based on the quantum confined Stark effect. When the project is powered on, the frequency wavelength of the laser will change before and after the acceleration load due to the quantum confined Stark effect, and the magnitude of the acceleration can be sensed through the difference frequency.
[0005] The present invention is an optomechanical microcavity accelerometer based on the quantum restricted Stark effect, with a silicon-based nitride epitaxial wafer as a carrier, comprising a silicon substrate layer, an aluminum nitride layer, a u-type gallium nitride layer, an n-type gallium nitride layer, a quantum well layer, a p-type gallium nitride layer, a SiO2 layer, a p-type electrode arranged on the p-type gallium nitride layer, and an n-type electrode arranged at the edge of the n-type gallium nitride layer, all of which are etched away above the silicon substrate layer, leaving only the square disk and the portion below the beam, so that the shape of the beam and the square disk is exposed, and the n-type electrode is arranged on the upper side of the exposed n-type gallium nitride layer.
[0006] Furthermore, the accelerometer of the present invention comprises a beam with a mass block in the middle, which is located in the middle of the device.
[0007] Furthermore, in the accelerometer of the present invention, when powered on, before and after the acceleration load, the frequency wavelength of the laser will change due to the quantum confined Stark effect, and the magnitude of the acceleration will be sensed through the difference frequency.
[0008] The present invention utilizes optical lithography and ICP etching process to prepare an accelerometer with a single beam, and designs reasonable process steps, including etching the shape of a template, to obtain a single beam supported by a columnar shape and having a smooth edge.
[0009] The present invention provides a method for preparing an InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect, comprising the following steps: Step 1: Spin-coat photoresist on the p-type GaN surface of the GaN-on-Si epitaxial wafer, and then use optical lithography to define a pattern of two square disks connected by a beam on the spin-coated photoresist layer; Step 2: Use electron beam evaporation technology to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, then put the epitaxial wafer into acetone solution for ultrasonic treatment, then put the epitaxial wafer into ultrapure water for cleaning, and then put it into anhydrous ethanol and ultrapure water for cleaning in turn, and finally remove the residual photoresist; a mask pattern of nickel is obtained.
[0010] Step 3: Etch down 2 μm-2.5 μm to the middle of the n-type gallium nitride layer using ICP etching technology, so as to transfer the pattern defined in the first step to the n-type gallium nitride layer of the silicon-based nitride epitaxial wafer to obtain the structure of a beam of the accelerometer; Step 4: Use dilute nitric acid to remove metallic nickel, then immediately rinse in ultrapure water; Step 5: Evaporate the SiO2 layer on the middle beam of the accelerometer, but do not evaporate the SiO2 layer on the small square at one quarter of the beam.
[0011] Step 6: Spin-coat photoresist on a beam of the accelerometer and the surrounding surface to ensure that the beam structure and the periphery will not be etched during the etching process, which plays a protective role; Step 7: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, and then the epitaxial wafer is placed in an acetone solution for ultrasonic cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed to obtain a mask pattern of nickel; Step 8: Use ICP etching technology to etch the pattern downward until the middle is hollowed out, and finally clean the remaining photoresist; Step 9: Using electron beam evaporation technology to evaporate a positive electrode on the upper surface of the p-type region electrode pattern, and to evaporate a negative electrode on the upper surface of the n-type region electrode pattern, so that the p-type gallium nitride layer and the n-type gallium nitride layer are respectively plated with positive and negative electrodes, and finally the residual photoresist is removed to obtain the p-type region electrode and the n-type region electrode; Step 10: Use a mixture of hydrofluoric acid and dilute nitric acid to wet-etch silicon until the bottom of the silicon substrate layer, so that silicon columns and a bottom surface supporting this structure are formed in the silicon substrate layer to form a suspended beam structure.
[0012] Furthermore, the positive electrode and the negative electrode are both evaporated Au / Ni.
[0013] Beneficial effects: Compared with the prior art, the present invention has the following advantages: 1. The present invention uses a single epitaxial wafer, does not need to grow different materials, has a simple structure, small size, and is easy to integrate. Compared with the current optical accelerometers made of passive materials such as SI and SIN, it has the advantages of miniaturization, low cost, high sensitivity, anti-electromagnetic interference, and impact resistance. 2. This project designs a single laser on an electrically pumped InGaN quantum well beam to construct an optomechanical microcavity accelerometer. Under acceleration load, the piezoelectric polarization field caused by the mechanical strain of the beam induces the quantum confined Stark effect of the quantum well, causing the laser frequency wavelength of the electrically pumped beam laser to change, and the magnitude of the acceleration is sensed by the change in frequency wavelength. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Side view of the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect Figure 2 Top view of the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect.
[0015] Figure 3 Process flow chart of InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect.
[0016] Figure 4 Stress distribution on the accelerometer surface under the net gravity field.
[0017] Figure 5 Displacement deformation of the middle beam of the accelerometer under the net gravity field.
[0018] In the figure, there are: 1-silicon substrate layer, 2-aluminum nitride layer, 3-u-type gallium nitride, 4-n-type gallium nitride layer, 5-quantum well layer, 6-p-type gallium nitride layer, 7-SiO2 layer, 8-p-type electrode, 9-n-type electrode, 10-stress sensitive area, 11-beam. DETAILED DESCRIPTION
[0019] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the accompanying drawings, and the words "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively.
[0020] Example 1: Figure 1-2As shown, an InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect of this embodiment uses a silicon-based nitride epitaxial wafer as a carrier, and includes a silicon substrate layer 1, an aluminum nitride layer 2, a u-type gallium nitride layer 3, an n-type gallium nitride layer 4, a quantum well layer 5, a p-type gallium nitride layer 6, and a SiO2 layer 7 arranged in sequence from bottom to top, a p-type electrode 8 arranged on the p-type gallium nitride layer 6, and an n-type electrode 9 arranged at the edge of the n-type gallium nitride layer 4, and the silicon substrate layer 1 retains a middle beam 11; after power is turned on, the stress sensitive area 10 of the beam will emit laser LD.
[0021] This accelerometer is a rectangular ring connected by a beam with a mass block in the middle, and the two squares on both sides of the beam are hollowed out; the p-electrode 8 is composed of a beam and a square electrode, and there is a mass block in the middle of the beam; the stress-sensitive area 10 of the beam is not evaporated with a SiO2 layer, and the rest is coated with a layer of SiO2 layer 7, and the p-type electrode 8 is deposited on the upper surface of the SiO2 layer 7 on the middle beam; the n-type electrode 9 is deposited on the n-type gallium nitride layer 4 on the other side and is a square electrode.
[0022] The stress sensitive area 10 occupies one quarter of the length of the beam 11 ; and when the beam 11 is powered on, only the stress sensitive area 10 will emit laser LD.
[0023] This embodiment uses a silicon-based nitride epitaxial wafer as a carrier, and from bottom to top, there are a silicon substrate layer, an aluminum nitride layer, a u-type gallium nitride layer, an n-type gallium nitride layer, a quantum hydrazine layer, a p-type gallium nitride layer, a SiO2 layer, and a p-type electrode arranged on the p-type gallium nitride layer and a square n-type electrode arranged on the edge of the n-type gallium nitride layer. The silicon substrate layer is completely etched away, leaving only the middle beam and the lower part around the accelerometer, and the n-type electrode is arranged on the side of the exposed n-type gallium nitride layer. The accelerometer is provided with a beam with a mass block located between two square disks. The beam width is 20μm. The accelerometer covers the p-type electrode of the p-type gallium nitride layer, and the p-type electrode consists of a beam and a square electrode. The beam length is 300μm, the square electrode is 30μm long and 20μm wide, and the electrode thickness is 120nm.
[0024] like Figure 3 As shown, the method for preparing the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect of this embodiment, the preparation process is as follows: Step 1: Clean the purchased commercial silicon substrate GaN epitaxial wafer with acetone, anhydrous ethanol and ultrapure water in sequence by ultrasonic cleaning (5 minutes), and then blow dry with nitrogen; use a coating machine to spin-coat the front side of the epitaxial wafer (the upper surface of the p-type nitride layer 5) with photoresist AZ-5214 at a speed of 4000 rpm for 40 seconds (the thickness of the photoresist is 1.5 microns).
[0025] Optical lithography technology is used, and then optical lithography technology is used to define two square patterns connected to a beam with a mass block on the spin-coated photoresist layer. The lithography machine model is MA6.
[0026] Step 2: Use electron beam evaporation technology to evaporate 350nm of metal nickel on the surface of the P-type gallium nitride layer 6, and then remove the residual photoresist.
[0027] Step 3: Etch the nitride layer downwards to the n-type gallium nitride layer 4 using ICP etching technology, so as to transfer the pattern defined in the first step to the n-type gallium nitride layer 3 of the silicon-based nitride epitaxial wafer, and obtain a beam structure of the accelerometer; The epitaxial wafer is then placed in a dilute nitric acid solution to remove the residual metallic nickel, and then placed in anhydrous ethanol and ultrapure water to clean it; Step 4: Evaporate a SiO2 layer on a beam in the middle of the accelerometer, but do not evaporate a SiO2 layer on a small square at the tail of the beam.
[0028] Step 5: Use a coating machine to spin-coat the front side of the epitaxial wafer (the surface of a beam structure and the surrounding square surfaces) with a speed of 4000 rpm and a spin coating time of 40 seconds (the thickness of the photoresist is 1.5 μm).
[0029] Step 6: Use electron beam evaporation technology to evaporate 420nm of metal nickel on the surface of the n-type gallium nitride layer 4, and then remove the residual photoresist.
[0030] Step 7: Use ICP etching technology to etch the pattern downward until the middle is hollowed out; The epitaxial wafer is then placed in a dilute nitric acid solution to remove the residual metallic nickel, and then placed in anhydrous ethanol and ultrapure water to clean it; Step 8: Use a mixture of hydrofluoric acid and dilute nitric acid to wet-etch silicon until the bottom of the silicon substrate layer 1, so that a silicon column and a bottom surface supporting this structure are formed in the silicon substrate layer 1, so that a beam structure of the LD is suspended. The etching gas is a mixture of HF and HNO3, the etching time is 1 minute, and finally remove the residual photoresist.
[0031] COMSOL Multiphysics is a multi-physics simulation platform involving multiple modules such as fluid, electromagnetic, heat transfer, structure, chemical engineering, acoustics, equations, etc. It only needs to give the coupling relationship with the physical field in various scenarios to express it using the software. This invention was simulated using this software.
[0032] The device is studied in a steady state under a net gravity field, and the stress distribution on the device surface is shown in Figures 4 and 5. It can be found that the stress at one quarter of the beam is significantly greater than the stress around it.
Claims
1. An InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect, characterized in that: The accelerometer uses a silicon-based nitride epitaxial wafer as a carrier, and comprises a silicon substrate layer (1), an aluminum nitride layer (2), a u-type gallium nitride layer (3), an n-type gallium nitride layer (4), a quantum well layer (5), a p-type gallium nitride layer (6), and a SiO2 layer (7) arranged in sequence from bottom to top; a p-type electrode (8) arranged on the p-type gallium nitride layer (6); and an n-type electrode (9) arranged at the edge of the n-type gallium nitride layer (4); and a middle beam (11) is retained in the silicon substrate layer (1); after power is applied, a stress sensitive region (10) of the beam emits laser light LD.
2. The InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect according to claim 1, characterized in that: The accelerometer is a rectangular ring connected in the middle by a beam with a mass block, and the two square blocks on both sides of the beam are hollowed out; the p-electrode (8) is composed of a beam and a square electrode, and there is a mass block in the middle of the beam; the stress sensitive area (10) of the beam is not evaporated with a SiO2 layer, and the rest is coated with a layer of SiO2 layer (7); the p-type electrode (8) is deposited on the upper surface of the SiO2 layer (7) on the middle beam; the n-type electrode (9) is deposited on the n-type gallium nitride layer (4) on the other side and is a square electrode.
3. The InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect according to claim 1, characterized in that: The stress sensitive area (10) occupies one quarter of the length of the beam (11).
4. The InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect according to claim 1, characterized in that: When the beam (11) is energized, only the stress sensitive area (10) will emit laser LD.
5. According to claim 3, according to the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect according to claim 1, before and after the acceleration load, the frequency wavelength of the laser will change due to the quantum confined Stark effect, and the magnitude of the acceleration will be sensed through the difference frequency.
6. A method for preparing an InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect, characterized in that: The method comprises the following steps: Step 1: Spin-coat photoresist on the p-type GaN surface of the GaN-on-Si epitaxial wafer, and then use optical lithography to define a pattern of two square disks connected by a beam on the spin-coated photoresist layer; Step 2: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the upper surface of the defined pattern, and then the epitaxial wafer is placed in an acetone solution for ultrasonic treatment, and then the epitaxial wafer is placed in ultrapure water for cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed; a mask pattern of nickel is obtained; Step 3: Etch down 2 μm-2.5 μm to the n-type gallium nitride layer using ICP etching technology, so as to transfer the pattern defined in the first step to the n-type gallium nitride layer of the silicon-based nitride epitaxial wafer to obtain the structure of a beam of the accelerometer; Step 4: Use dilute nitric acid to remove metallic nickel, then immediately rinse in ultrapure water; Step 5: Evaporate the SiO2 layer on the middle beam of the accelerometer, but do not evaporate the SiO2 layer on the small square at one quarter of the beam; Step 6: Spin-coat photoresist on a beam of the accelerometer and the surrounding surface to ensure that the beam structure and the periphery will not be etched during the etching process, which plays a protective role; Step 7: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, and then the epitaxial wafer is placed in an acetone solution for ultrasonic cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed to obtain a mask pattern of nickel; Step 8: Use ICP etching technology to etch the pattern downward until the middle is hollowed out, and finally clean the remaining photoresist; Step 9: using electron beam evaporation technology to evaporate a positive electrode on the upper surface of the p-type region electrode pattern and to evaporate a negative electrode on the upper surface of the n-type region electrode pattern, so that the p-type gallium nitride layer (6) and the n-type gallium nitride layer (4) are respectively coated with positive and negative electrodes, and finally removing the residual photoresist to obtain a p-type region electrode (8) and an n-type region electrode (9); Step 10: Wet-etch silicon using a mixture of hydrofluoric acid and dilute nitric acid until the bottom of the silicon substrate layer (1), so that silicon columns and a bottom surface supporting the structure are formed in the silicon substrate layer (1), forming a suspended beam structure.
7. The method for preparing an InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect according to claim 6, characterized in that: The positive electrode and the negative electrode are both evaporated Au / Ni.
Citation Information
Patent Citations
Si based HEMT embedded micro accelerator and production method thereof
CN102401840A
Electric pumping optical gyroscope and preparation method thereof
CN113418519A
Electric pump acceleration sensor and preparation method thereof
CN113624992A
On-chip InGaN quantum hydrazine beam triaxial accelerometer based on electric pump and preparation method thereof
CN116477562A
White light LED based on quantum limited stark effect and preparation method thereof
CN116613254A
Cited By
InGaN difference frequency accelerometer with quantum limited stark effect and preparation method thereof
CN120722010A
InGaN opto-electro-mechanical accelerometer with quantum-limited stark effect and preparation method of InGaN opto-electro-mechanical accelerometer
CN120722011A